(untitled) (Altre Modernità, 2017)
Harry Potter is a very successful series of novels, mainly addressed to children and adolescents. The story is set in a magical world, parallel to our own; it revolves around the lives of the young wizard Harry Potter and his friends, each novel narrating a year of their lives as they go to school, study the magic arts, and fight against the evil wizard Voldemort (Harry Potter and the Philosopher’s Stone, 1997; Harry Potter and the Chamber of Secrets, 1998; Harry Potter and the Prisoner of Azkaban, 1999; Harry Potter and the Goblet of Fire, 2000; Harry Potter and the Order of the Phoenix, 2003; Harry Potter and the Half-Blood Prince, 2005; Harry Potter and the Deathly Hallows, 2007).